Industrial Role Optimization in Regional Development through Corporate Social Responsibility - Puji Handayati; Budi Eko Soetjipto; Dhika Maha Putri; Ria Zulkha Ermayda; Sulis Rochayatun; Ratna Dwi Nastiti; Bagus Shandy Narmaditya; Shadi Emad Areef Alhaleh (Universitas Negeri Malang, 2020)
Sustainable development is a complex problem that demands a partnership to create synergy from government and the industrial sector. This partnership is created through corporate social responsibility (CSR) program with the sustainable development principle. East Java, one of the provinces in Indonesia, has developed CSR forums in the regencies/cities to synergize the company’s CSR programs with the regional development programs. This study aims to minutely examine how the industrial world optimally performs its role in regional development with its social responsibility. This research used the content analysis method, while the respondents were 18 CSR Forums out of regencies/cities in East Java, and companies incorporated in those forums. The results showed that most of the companies had carried out their social responsibilities with variations in their numbers and activities. A report said that three trillion rupiah were granted for the CSR fund. It was a significant amount compared to the 30 trillion development budgets of East Java in 2018. The implementation of CSR tends to be charity, instead of be directed and arranged into continuous and sustainable programs. The CSR Forums are to perform a proactive synergy between companies and the government. However, due to various limitations and constraints of each region, this has not reached its optimal level. Ongoing efforts are needed to establish government and industry harmonization with the intention that the existing CSR funds unquestionably become one of the regional development reinforcements. Keywords: Corporate Social Responsibility (CSR), CSR Forum, Regional Development